PROSPECTS FOR SCIENTIFIC AND TECHNICAL DEVELOPMENT OF OUTLINE DESIGN OF UKRAINIAN OCEANOGRAPHIC NEW GENERATION RESEARCH VESSEL - O.A. Shchyptsov; O.O. Shchyptsov (Геологія і корисні копалини Світового океану, 2019)
The article discusses the prospects of developing outline design of Ukrainian oceanographic new generation research vessel. In particular, there are described issues of general requirements formation for the design, architecture and equipment of a new generation multifunctional oceanographic research vessel for its operation in the AzovBlack Sea basin, taking into account the set scientific and technical tasks for the oceanographic and hydrographic research of the marine environment of the AzovBlack Sea basin, as well as the specifics of creating complex of ship research laboratories (on a modular basis) for a vessel of the specified type. There is presented a list of scientific and technical tasks for oceanographic and hydrographic research of the marine environment of the AzovBlack Sea basin, the implementation of which is possible via using a universal oceanographic research vessel. There are described issues of creating a complex of vessel research laboratories of an oceanographic research vessel on a modular basis, as well as the formation of an appropriate generalized technical proposal. The general characteristics of the research vessel «Mintis» of Klaipeda University (Lithuania) are presented as an example of a modern oceanographic research vessel.